FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA 4 (EMPAT) BANK ASET TERBESAR DI INDONESIA PERIODE 2017–2021 - Hartanto, Hartanto (Ekonis: Jurnal Ekonomi dan Bisnis, 2024)
Abstract: The purpose of this research is to examine and analyze the effect of fundamental factors: Net Interest Margin, Loan to Deposit Ratio, Earning Per Share and Net Income on Stock Prices. This research method is a causal research design. The research was conducted on 4 (four) banks with the largest assets in Indonesia which were listed on the Indonesia Stock Exchange in 2017-2021. The statistical test tool used is a multiple linear regression model. The results of this research show that Earning Per Share has a significant and positive effect on stock prices, while Net Interest Margin, Loan to Deposit Ratio and Net Income have no effect on stock prices. Keywords: Net Interest Margin (NIM), Loan to Deposit Ratio (LDR), Earning Per Share (EPS), Net Income, Stock Price.